Craniofacial anthropometric norms of Malays - Ngeow, W. C.; Aljunid, S. T. (SINGAPORE MEDICAL ASSOC, LEVEL 2 ALUMNI MEDICAL CENTRE, 2 COLLEGE RD, SINGAPORE 169850, SINGAPORE, 2009)
Introduction: This study was undertaken to establish the craniofacial anthropometric norms of young adult Malaysian Malays. Methods: The study group consisted of convenient samples of 100 healthy volunteers (aged 18-25 years), with an equal number of female and male subjects who had no history of mixed racial parentage. 22 linear measurements were taken twice from 22 landmarks over six craniofacial regions. Results: The Malays shared many similar sizes of measurements with the Singaporean Chinese. Their left eye fissure length and mouth width (ch-ch) were almost identical for both genders. However, Malay females had an upper lip height (sn-sto) (left) and ear width (pra-pa) similar to Singaporean Chinese females. Six other measurements, viz. the head width (eu-eu), head circumference (on-op), face height (n-gn), lower face height (sn-gn), (left) eye fissure height (ps-pi), cutaneous upper lip height (sn-ls) and cutaneous upper lip height (ls-sto), were 0.4-4.3 mm less in the Malays. Measurements for another four parameters, viz. the length of the head (g-op), biocular width (ex-ex), lower vermillion height (sto-li) and (left) ear length (sa-sba), were 0.5-3.6 mm higher in the Malays. Only three measurements were obviously different; the height of the head (vn) and intercanthal width (en-en), were lower, and the protrusion of the nasal tip (sn-prn) was higher in the Malays. Conclusion: These findings suggest that three features, i.e. the height of the head (v-n), intercanthal width (en-en) and protrusion of the nasal tip (sn-prn) may be useful in differentiating a Malay face from a Singaporean Chinese one.